MODERNIZATION OF THE FINANCIAL RESOURCE MANAGEMENT ALGORITHM OF MILITARY UNITS BASED ON THE PERSONAL INCOME TAX RETURN MECHANISM - Panuchnyk, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . T h e o rganization of effective financial support for military units is a critically important imperative of Ukraine’s defense strategy in the context of a full-scale invasion. In this regard, the mechanism of transferring a portion of personal income tax to the budgets of military units emerges as a tool that determines the efficiency of responding to urgent needs, optimizing the use of resources, and ensuring transparency in financial flows. At the same time, its application requires deep theoretical understanding, modeling of management processes, and development of an algorithm for using these funds within an uncertain security environment. M e t h o d s . The study is based on a comprehensive methodological approach that integrates the analysis of the effectiveness of Ukrainian regulatory legal acts on personal income tax returns, a comparative study of international experience in financing and localizing defense units, and the systematization of empirical data on the use of returned funds in military units since 2022. General scientific methods of cognition, abstraction, logical generalization, systematization, case analysis and graphic visualization were employed. The application of contextual analysis enabled the integration of empirical-phenomenological and abstract-theoretical levels. R e s u l t s . The results indicate that the systematic application of the personal income tax return mechanism enables military units to timely cover their needs for material and technical procurement, pay for services, and organize logistical support. Based on the analysis, key components of the algorithm were identified, including institutional modernization, management mechanisms, and management tools. In particular, the study demonstrated that the integration of digital solutions, the use of blockchain registries, and plan-fact analysis enhance transparency and significantly reduce the risks of fund misuse. C o n c l u s i o n s . The proposed conceptual approach to modernizing the algorithm for managing the financial resources of military units through the personal income tax return mechanism lays the foundation for the financial autonomy and operational efficiency of units under wartime conditions. Its scientific novelty lies in the integration of legal, organizational, and digital components into a holistic system of the country’s financial security. The practical significance of the study is manifested in the development of recommendations aimed at optimizing budget processes, ensuring control and transparency of expenditures, and promoting institutional consolidation of participatory financial management practices in Ukraine’s security and defense sector.